A comprehensive review of environmental design in UK schools: History, conflicts and solutions. (June 2015) - Montazami, Azadeh; Gaterell, Mark; Nicol, Fergus
Abstract: The health and performance of students and teachers are influenced by the internal environment of school buildings such as noise levels, indoor temperature, air quality and light. Providing good internal environmental conditions with minimum energy for schools has long been a concern in school design guidelines around the world. The growing necessity to save energy in an uncertain future and to provide a good indoor environment in schools suggests that school designers should approach design more holistically in order to offer a better internal environment and to reduce the gap between design and performance. This paper investigates design issues in UK schools through case study analysis and a review of the literature. The main reasons for these design issues can be attributed to the lack of optimisation of different internal environment factors and their relation with energy consumption; the lack of understanding occupants' response to the environment; the lack of building adaptability and the inappropriate application or use technology. This paper urges school designers to look at these factors holistically in order to overcome these problems in the future design of UK schools. This study also suggests an Environmental Circle to look at the interrelation between comfort factors through their sub factors in a holistic manner in order to prevent any conflict between.